2012
DOI: 10.3109/00365521.2012.660538
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone disease is associated with rectal cancer: a meta-analysis

Abstract: Cholelithiasis increases the risk of rectal cancer. No association exists between cholecystectomy and rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…3,8,36 The status post cholecystectomy was also related to hepatic cancer, colorectal cancer, and gastric cancer. 2,3,21,37,38 However, there are few studies that focused on cancer risks in cholecystitis.…”
Section: Specific Cancer Typesmentioning
confidence: 98%
“…3,8,36 The status post cholecystectomy was also related to hepatic cancer, colorectal cancer, and gastric cancer. 2,3,21,37,38 However, there are few studies that focused on cancer risks in cholecystitis.…”
Section: Specific Cancer Typesmentioning
confidence: 98%
“…A meta-analysis of 42 studies encompassing 14226 incident cases showed no significant risk of rectal cancer following cholecystectomy (OR = 1.14, 95%CI: 0.92-1.41) [70] . This finding is supported by three other case-control studies [53,62,63,65] and two cohort studies [56,64] .…”
Section: Rectal Cancermentioning
confidence: 99%
“…Six studies (4 case-control; 2 cohort) demonstrated a positive association between proximal colon cancer and cholecystectomy [59,62,63,[67][68][69][70][71][72][73][74][75][76][77][78][79] . An extremely high association (OR = 5.85, 95%CI: 2.13-16.7) was found in one particular Chinese study but 95%CIs were broad and a low quality assessment score indicates these findings are somewhat unreliable [62] .…”
Section: Proximal Colon Cancermentioning
confidence: 99%
“…Goldach et al conclude that cholecystectomy does not cause cancer [15]. Chiong suggests that cholelithiasis increases the risk of rectal cancer, and cholecystectomy does not infl uence this pathology [16]. Schmidt et al obtained inconclusive results to draw a fi rm conclusion [17].…”
Section: Discussionmentioning
confidence: 99%